Silent Competition among Students: How Schadenfreude and Social Envy Influence Rating-based Achievement Motivation - Bilson Simamora (Universitas Ahmad Dahlan, 2021)
Schadenfreude and social envy have attracted human interest for thousands of years. However, little is know about how they influence achievement motivation in a hierarchical and competitive social environment. To overcome this problem, inspired by Mayer and Saloveyâ€™s (1997) emotional intelligence theory, the author develops rivals' anticipated emotions (RAE) and models how the sense of being envied and become the schadenfreude target influence the motivation to avoid the decrease of or to increase current competitive position.Â The study follows Higgin's (1997) self-regulatory framework in students' context. In the schadenfreude scenario, as part of self-protection, the study proposes that the sense of being a schadenfreude target, represented by rivals' anticipated joyfulness (RAJ), influences students' motivation to avoid the decrease of current competitive position (prevention focus), especially for those who occupy upper and medium positions. Rivals' anticipated distress (RAD) that represents the sense of being envied stimulates students' motivation to increase competitive position (promotion focus), especially for those who occupy the lower and medium position. When working together, the RAJ and RAD stimulate promotion and avoidance motivations simultaneously, especially among mediocre students. Future researchers can widen their investigation into intergroup schadenfreude and social envy research domains.Â